Geodiversity and Geoconservation in Yuanmou Basin, Yunnan Province, China. Issue 1 (November 2021) - Cheng, Xianfeng; Qi, Wufu; He, Ping; Zhang, Shitao; Shi, Liang
Abstract: Geodiversity is considered as abiotic diversity, and it is the foundation of geopark, geotourism and geoconservation. Yunnan Province is the typical area abundant in geodiversity in China. Geodiversity of Yuanmou Basin, which is located in North Yunnan, possesses scientific, cultural, aesthetical, ecological values. Howerver, there are some problems, such as underexploitation, inadequate protection, even destruction in the area. Research of geodiversity will provide a new idea for sustainable development in Yuanmou Basin.